Some Quaries of Allama Iqbal from Maulana Rumi - Khalid Mahmood Sanjrani (بازیافت, 2018)
Allama Iqbal's Urdu poem "Peer o Mureed" reflects the imaginative dialogue between Maulana Rumi and Allama Iqbal in which Allama Iqbal seek guidance from Rumi on various subjects of his times. Allma Iqbal concidered Rumi as his "Murshid" specially in his persian poetry. This paper deals with an Urdu poem in which Allama Iqbal raised some important questions related with the contemporary situation of the Muslims .